Subjectivity in inductive inference - Larry Samuelson; Itzhak Gilboa (Theoretical Economics, 2012)
This paper examines circumstances under which subjectivity enhances the effectiveness of inductive reasoning. We consider agents facing a data generating process who are characterized by inference rules that may be purely objective (or data-based) or may incorporate subjective considerations. The basic intuition is that agents who invoke no subjective considerations are doomed to "overfit" the data and therefore engage in ineffective learning. The analysis places no computational or memory limitations on the agents|the role for subjectivity emerges in the presence of unlimited reasoning powers.
Keywords: C1; D8; 330; Inductive inference; simplicity; prediction; learning